High thermoelectric and electronic performance in graphene nanoribbons by isotope and vacancy engineering. (2018) - Tran, Van-Truong; Saint-Martin, Jérôme; Dollfus, Philippe; Volz, Sebastian
Abstract: We study the effects of isotope doping and vacancies on the electronic, phononic and thermoelectric properties of graphene nano-ribbons by means of atomistic simulation based on semi-empirical Tight Binding and Force Constant models combined with the Non-Equilibrium Green's Function formalism of transport. We demonstrate that from the phononic perspective, the impact of isotope doping on transmission is very dependent on the phonon frequency and particularly strong at high frequency, while vacancies wield their influence on the whole frequency range. From the electronic point of view, if placed at dimer line positions m = 3 i + 1, 3 i + 2, vacancies induce a strong reduction of the electrical conductance while vacancies at positions m = 3 i act as isotopes, i.e. they are transparent to electrons and do not affect the electronic properties. The thermoelectric study is conducted by combining both electronic and phononic properties. It demonstrates the possibility of a remarkable enhancement of figure of merit ZT . In the presence of both types of defects, ZT can be enhanced significantly from 0.26 in pristine ribbons to values larger than 2.5 for ribbons of width M = 5.